1996
DOI: 10.1021/om9508445
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Highly Unsaturated Anionic Tetrahydridononacarbonyltrirhenate Cluster

Abstract: The reaction between H4Re4(CO)12 and N,N-dimethylformamide (DMF) in chloroform yields [H4Re3(CO)9]-[Re(CO)3(DMF)3]+, 1, quantitatively. The X-ray structure of 1 reveals that the three Re atoms in the 44-e anionic cluster [H4Re3(CO)9]- form an isosceles triangle. Two hydrides bridge the two long Re−Re single-bonded edges, and another two hydrides bridge the Re−Re double-bonded edge. There is a coordinative unsaturation site on the rhenium atom not involved in the Re−Re double bond. However, the anionic cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The reaction between H 4 Re 4 (CO) 12 and N,N-dimethylformamide (DMF) yields [H 4 Re 3 (CO) 9 -][Re(CO) 3 (DMF) 3 + ] (1) quantitatively. 4 In chloroform or dichloromethane solution with This DMF-coordinated cluster, with its extra ligand coordinated to the rhenium atom not connected to others by a Re-Re double bond, is isostructural with H 4 Re 3 (CO) 10 -7 and H 4 Re 3 (CO) 9 (PPh 3 ) -. 8 It was found that the chloroform solution of 1 with a DMF concentration of 0.13 M turned from yellow to reddish yellow on standing for 24 h at 298 K. A yellow crystalline precipitate, 2, can be obtained from this solution.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The reaction between H 4 Re 4 (CO) 12 and N,N-dimethylformamide (DMF) yields [H 4 Re 3 (CO) 9 -][Re(CO) 3 (DMF) 3 + ] (1) quantitatively. 4 In chloroform or dichloromethane solution with This DMF-coordinated cluster, with its extra ligand coordinated to the rhenium atom not connected to others by a Re-Re double bond, is isostructural with H 4 Re 3 (CO) 10 -7 and H 4 Re 3 (CO) 9 (PPh 3 ) -. 8 It was found that the chloroform solution of 1 with a DMF concentration of 0.13 M turned from yellow to reddish yellow on standing for 24 h at 298 K. A yellow crystalline precipitate, 2, can be obtained from this solution.…”
Section: Resultsmentioning
confidence: 98%
“…Formation of the Novel Square-Pyramidal Anionic Cluster H 7 Re 5 (CO) 1 5 2- . The reaction between H 4 Re 4 (CO) 12 and N , N -dimethylformamide (DMF) yields [H 4 Re 3 (CO) 9 - ][Re(CO) 3 (DMF) 3 + ] ( 1 ) quantitatively . In chloroform or dichloromethane solution with high DMF concentration (>1 M), 1 does not undergo any cluster skeletal transformation, because the anionic cluster H 4 Re 3 (CO) 9 - is coordinated by DMF: This DMF-coordinated cluster, with its extra ligand coordinated to the rhenium atom not connected to others by a Re−Re double bond, is isostructural with H 4 Re 3 (CO) 10 - and H 4 Re 3 (CO) 9 (PPh 3 ) - …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The μ 2 -bridging coordination is much more common 7 and often involves agostic interactions . In triangular clusters it has been observed in [Os 3 (μ-H)(μ-HCH 2 )(CO) 10 ] 9 and in [Re 3 (μ-CH 3 ) 3 (CH 3 ) 6 (PEt 2 Ph) 2 ] …”
Section: Referencesmentioning
confidence: 99%